Beyond EU-US Trade Dynamics: TTIP Effects Related to Foreign Direct Investment and Innovation - Andre Jungmittag; Paul J. J. Welfens (Institute of Labor Economics (IZA), 2017)
The international economic debate on the Transatlantic Trade and Investment Partnership (TTIP) has focused mainly on trade induced real income gains while the FDI related and innovation induced benefits have been largely neglected, although the EU and the US are leading FDI host countries and FDI source countries. Moreover, from a theoretical perspective a knowledge production function has to be considered in order to analyze FDI and innovation dynamics – and this can then be linked to output and economic growth, respectively. It is argued that such a Schumpeterian approach for an open economy is needed to understand deep integration dynamics while the standard CGE model used by Francois et al (2013) leads to an underestimation of deep integration projects such as TTIP. The panel data estimation of knowledge production functions for 20 EU countries between 2002-2012 shows clear empirical evidence that a rise of the number of researchers and of the FDI stock-GDP ratio (or related variables) will raise patent applications. Additionally, a higher per capita income – that could reflect trade related real income gains in the context of TTIP – also contributes to new knowledge and a fortiori to higher GDP. Time series data analysis for Germany indicates additionally that FDI induced higher innovation dynamics will raise output – combining trade benefits and FDI/innovation related real income gains plus transatlantic macroeconomic interdependency effects a real income gain of nearly 2% should be expected for Germany (and the EU): considerably higher than what the official TTIP report for the European Commission has suggested. The results also suggest positive employment effects.
Keywords: F14; F43; O30; O47; O52; 330; knowledge production function; innovation; FDI; TTIP; empirical analysis; EU